Essentials of advanced macroeconomic theory - Olsson, Ola (Routledge, 2012)
rying to summarize the essentials of macroeconomic theory in the wake of the financial crisis that has shaken not only Western economies but also the macroeconomic profession is no easy task. In particular, the notion that markets are self-correcting and always in equilibrium appears to have taken a heavy blow. However, the jury is still out on which areas should be considered as failures and what which constitute the future of research.